Apparatus for ammonia removal in livestock farms based on copper hexacyanoferrate granules. (April 2022) - Minami, Kimitaka; Takahashi, Akira; Sakurai, Koji; Mikasa, Hiroaki; Takasaki, Mikihiro; Doshu, Naoaki; Aoyama, Katsuya; Nakamura, Tohru; Iwai, Ryota; Kawamoto, Tohru
Abstract : Ammonia generated by livestock is a source of strong odour and pollution. In livestock management, ammonia negatively impacts not only animal health, but also productivity. A large-capacity and high-selectivity ammonia adsorbent that can be regenerated with water or dilute acids has been previously developed. In this study, ammonia adsorption and adsorbent regeneration apparatuses using this adsorbent are constructed and tested for ammonia removal in a pig house. The ammonia adsorption apparatus adsorbed approximately 0.36 mol of ammonia per hour, and the adsorbent regeneration apparatus desorbed approximately 75% of ammonia adsorbed to the saturated adsorbent over four days. These systems allowed ammonia concentration and temperature to be controlled in closed pigpens, and their effectiveness was verified by rearing 20 pigs in a 21.6 m 2 pigpen. In winter, the ammonia concentration in the experimental area was suppressed to 10 ppmv or less, even with low ventilation, and was 4–7 °C warmer than the open control area. As a result, the average daily weight gain of the pigs increased by approximately 9% and 7% compared to those of pigs in the closed and open control areas, respectively. In summer, the ammonia concentration was 45–70% lower than that of the closed control area. The feed conversion ratio of pigs in the research area was approximately 6% and 9% lower than those of pigs in the closed and open control areas, respectively. Highlights: New system regenerate 75% of the adsorbent in four days. Ammonia concentration of low-ventilation pigpens decreased to ≤10 ppmv in winter. Ammonia concentration reduced by 45–70% relative to a closed area in summer. Average daily gain of pigs increased by 9% compared to the control in winter.